Addressing conflict through collective action in natural resource management: A synthesis of experience - Ratner, Blake D.; Meinzen-Dick, Ruth S.; Hellin, Jonathan; Mapedza, Everisto D.; Unruh, Jon D.; Veening, Wouter; Haglund, Eric; May, Candace; Bruch, Carl (International Food Policy Research Institute, 2013)
The food security crisis, international “land grabs,” and new markets for environmental services have drawn renewed attention to the role of natural resource competition in the livelihoods of the rural poor. While significant empirical research has focused on diagnosing the links between natural resource competition and (violent) conflict, much less has focused on the dynamics of whether and how resource competition can be transformed to strengthen social-ecological resilience and mitigate conflict. Focusing on this latter theme, this review synthesizes evidence from a wide range of cases in Africa, Asia, and Latin America. Building on an analytical framework designed to enable such comparative analysis; we present several propositions about the dynamics of conflict and collective action in natural resource management, and a series of recommendations for action.